2001
DOI: 10.1080/00131880110081026
|View full text |Cite
|
Sign up to set email alerts
|

Secondary students' development as teachers over the course of a PGCE year

Abstract: Research has suggested that students pass through different concerns or stages in their development as teachers. Although some authors have suggested that concerns or stages are sequential, other research does not support sequential concerns or stages of development. The major purpose of this study was to look at the concerns of students at different times during a one year Postgraduate Certificate in Education (PGCE) course, particularly to identify any changes in concerns about school experience as they deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 15 publications
3
9
0
Order By: Relevance
“…However, other empirical studies have been unable to completely confirm developmental patterns of teacher concerns (Capel 2001;Ghaith and Shaaban 1999;Mok 2005;Pigge and Marso 1987). Other factors extend Fuller's concerns model.…”
Section: Graduate Teaching Assistants' (Gtas') Characteristics and Thmentioning
confidence: 88%
“…However, other empirical studies have been unable to completely confirm developmental patterns of teacher concerns (Capel 2001;Ghaith and Shaaban 1999;Mok 2005;Pigge and Marso 1987). Other factors extend Fuller's concerns model.…”
Section: Graduate Teaching Assistants' (Gtas') Characteristics and Thmentioning
confidence: 88%
“…Over the years, various studies have investigated different dimensions of pre-service teacher experiences, including their development of literacy practices (Estrada & Grady, 2011), concerns (Capel, 2001), mentoring experiences (Edwards, 1998), and how stress affects them (Head, Hill & Maguire, 1996). In a more recent investigation pertaining to pre-service teacher expectations, researchers have found that expectations appear to influence how pre-service teachers perceive preparedness at the end of their courses (Hobson, Giannakaki & Chambers, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Those Traditional PSTs that had done experiences outside the university, such as substitute teaching, and those PSTs in the SKyTeach program reflected that the previous experience allowed them to focus on the meticulous details of becoming a more effective teacher instead of being concerned about the superficial apprehensions of being in front of a classroom. These comments were in accordance with the findings of studies by Capel, (2001), Parsons (1973) and Petrusich, (1966) who stated that teachers with more experience tend to have fewer self-preservation concerns.…”
Section: Field Experience Effects On Concerns After Student Teachingsupporting
confidence: 80%
“…The findings that preservice teachers of different programs expressed similar levels of concerns coincide with the results of Dalez (1998) who compared the concerns of recent graduates of traditional teacher education program and graduates of a professional development school. Other studies which found simultaneous existences of teacher concerns among preservice teachers were reported by Capel (2001) and Evans and Tribble (1996). The presence of a moderate level of all three concerns before the student-teaching experience validated the idea that student teaching was a stressful time in a preservice teacher's program (Black-Branch & Lamont, 1998, Greer & Greer 1992.…”
Section: Concerns Of Preservice Teachersmentioning
confidence: 91%
See 1 more Smart Citation